Lightweight cement-free alkali-activated slag plaster for the structural retrofit and energy upgrading of poor quality masonry walls. (November 2019) - Coppola, L.; Coffetti, D.; Crotti, E.; Marini, A.; Passoni, C.; Pastore, T.
Abstract: The paper deals with the development of an innovative Portland-free lightweight structural plaster to improve the seismic performance and the energy efficiency of poor quality stone masonry buildings. In particular, one-part alkali-activated slag-based mortars were manufactured with different lightweight glass aggregate contents to be mechanically compatible with historic stone walls (28-day compressive strength up to 8 MPa) and to serve as a thermo-insulating layer (specific mass lower than 1000 kg/m 3 ). Results indicate that the Portland-free alkali activated-based plaster manufactured with expanded glass aggregates and air entraining agent is able to provide a 28-day compressive strength equal to 8 MPa and a thermal conductivity of 0.35 W/mK due to density close to 700 kg/m 3 . Moreover, by using methylcellulose (MC), modified starch (MS), polypropylene fibers, shrinkage reducing admixture (SRA) and silane-based surface treatment, it is possible to ensure an excellent adhesion to the substrate, the absence of micro-cracks and detachments and a very low water absorption coefficient.